Hubungan Shift Kerja dengan Stres Kerja dan Circadian Rhythm Perawat - Nursalam Nursalam; Arie Sunarno; Rahmatul Fitriyah (Jurnal Ners, 2007)
Introduction: Shift work, primarily night shift may worsen some health disturbances because it changes especially circadian rhythm. Therefore, it may lead to sleep disturbance, increased vital signs (heart rate, respiration rate and blood pressure), bowel disturbance, reaction times, conscious stage and increased work stress. The objective of this study was to analyze the correlation between shift work and Nurse’s circadian rhythm. Method: These study was cross sectional with nurses in Flamboyant Intermediate Surgical Ward Dr. Soetomo Hospital Surabaya as subjects. Samples were recruited by using total sampling and there were 15 samples as on inclusion criteria. Data were analyzed using Paired t-Test, Krusskall-Wallis, Wilcoxon, Mann-Whitney, Anova and Chi-Square with significance level α≤0.05. Result: The result showed that shift work had no correlation with nurses’ work stress (p=0.221). Nurses stress stage had no differences in three of shift (p=0.757). While shift work had correlation with nurse’s circadian rhythm disturbance (p=0.038) and night shift had differences circadian rhythm disturbance (p=0.038). Discussion: It can be concluded that there was correlation between shift work and circadian rhythm disturbance, however there is no correlation between shift work and work stress. Further studies are recommended to identify the dominant factor which cause work stress for nurses.